The web as a disposable corpus for conference interpreters: شبكة الإنترنت باعتبارها مجموعة يمكن التخلص منها لمترجمي المؤتمرات - Bazawsha , Elham (Maalim, 2024)
With the rapid advancement of technology, conference interpreters increasingly use the web as a disposable corpus to aid in their work. This paper examines how the web provides dynamic, accessible, and up-to-date linguistic data to support interpretation tasks. While it offers immediate access to relevant information, challenges such as the reliability of online content and ethical considerations arise. Through practical examples, the paper highlights how interpreters can integrate web resources into their workflow, enhancing their performance. It also addresses issues of data privacy and copyright compliance, advocating for the web’s potential to support continuous professional development in the digital age.